Potent and selective Bruton's tyrosine kinase inhibitors: Discovery of GDC-0834. Issue 6 (15th March 2015) - Young, Wendy B.; Barbosa, James; Blomgren, Peter; Bremer, Meire C.; Crawford, James J.; Dambach, Donna; Gallion, Steve; Hymowitz, Sarah G.; Kropf, Jeffrey E.; Lee, Seung H.; Liu, Lichuan; Lubach, Joseph W.; et al.
Graphical abstract